Results from a mobile drug checking pilot program using three technologies in Chicago, IL, USA. (1st November 2021) - Karch, Lydia; Tobias, Samuel; Schmidt, Clare; Doe-Simkins, Maya; Carter, Nicole; Salisbury-Afshar, Elizabeth; Carlberg-Racich, Suzanne
Highlights: Drug checking in mobile outreach is feasible and capable of detecting fentanyl. Discordant results were observed across technologies in opioid samples. Fentanyl detection in opioids ranged from 12.7% to 58.1% depending on technology used. Multiple technologies may enhance ability to identify fentanyl in local markets. Abstract: Background: Opioid overdose deaths in the United States continue to rise, with the majority of deaths involving fentanyl. Drug checking has been used in Europe and Canada to assess adulteration of the illegal drug supply, but faces legal barriers in the United States. We are presenting information from a pilot mobile program offering drug checking services to participants of a harm reduction program in Chicago, Illinois, USA. Methods: Drug checking services were provided at five mobile outreach and one fixed-point drop-in location in Chicago, IL, between March 2019 and August 2020. Three technologies were used: a Fourier transform infrared spectroscopy (FTIR) spectrometer, a handheld high-pressure mass spectrometer (HPMS), and immunoassay fentanyl test strips (FTS). We report on results generated by this combination of technology during the study period. Results: During the study period, 422 total samples were tested, the majority of which were sold as dope/heroin (66.7 %). Of the 282 samples sold as dope/heroin, 12.8 % matched to fentanyl on the FTIR, 47.5 % had fentanyl identified on the HPMS, and 57.8 % produced a positive FTS. Conclusions: This pilot program demonstrated the feasibility of using three technologies to assess for the presence of fentanyl in user-submitted samples, revealed discordant results from the technologies, and provided information on the local drug market.